A longitudinal follow-up of continuous laryngoscopy during exercise test scores in athletes irrespective of laryngeal obstruction, respiratory symptoms, and intervention - Irewall, T.; Bäcklund, C.; Naumburg, E.; Ryding, M.; Stenfors, N. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Exercise-induced laryngeal obstruction (EILO) is diagnosed by the continuous laryngoscopy during exercise (CLE) test. Whether or how much CLE test scores vary over time is unknown. This study aimed to compare CLE test scores in athletes over time, irrespective of respiratory symptoms and grade of laryngeal obstruction.